MEASURABLE KEY PERFORMANCE INDICATORS AS A TOOL FOR ASSESSING THE SUCCESS OF AN ORGANIZATION'S BUSINESS IMPLEMENTATION - Didit Darmawan; Seftia Ayuningsih; Muhammad Ricky Tirta Jagad Dhita; Rahayu Mardikaningsih; Arif Rachman Putra (International Journal Management and Economic, 2026)
This study examines the role of measurable key performance indicators (KPIs) as instruments for assessing the success of organizational business execution. Using a qualitative literature review approach, the study analyzes relevant scholarly works on performance measurement, strategic management, and KPI design to identify the principles underlying effective indicator selection, measurement, and use in managerial decision-making. The findings show that effective KPIs should possess relevance, validity, reliability, and sensitivity to change, while also maintaining direct alignment with organizational strategic objectives. KPI selection should be grounded in causal logic that links strategic actions to expected outcomes and should incorporate a balanced combination of leading and lagging indicators. The study also highlights the importance of limiting the number of indicators according to the principle of parsimony in order to maintain managerial focus on critical performance dimensions. In addition, realistic target setting, reliable data collection, validation procedures, and dashboard-based visualization are essential for improving the usefulness of performance information. The effectiveness of KPI systems further depends on the organization’s ability to interpret performance data, integrate it into formal decision-making processes, and use it to support accountability, organizational learning, and continuous improvement. This study contributes theoretically to the understanding of the relationship between performance measurement and strategic management, while practically offering guidance for organizations in designing KPI systems that support evidence-based evaluation of business execution.